A Comprehensive Analysis of Literately Research in Khyber Pakthunkhwa (DARYAFT, 2022)
The researcher of Khyber Pakhtunkhwa put their proper contribution in promoting Urdu Research in poetry, prose with special focus on linguistics, Ghalibiyat and Iqbaliyat has equally promoted in Urdu literature in this region. They are busy in their research work more than seven decades. A comprehensive detail of all the researchers i.e. from pioneer’s researcher (such as Farigh Bukhari, Raza Hamdani, Dr. Tahir Foorqi, Dr. Shams-du-Din Sadeqi, Khatir Ghaznave, Dr. Sabir Kalorvee, Basheer Soz, Dr. Irshad Ahmad Shakir Awan, Dr. Zahoor Ahmad Awan etc,) to present age, can be found in this article. The following article has comprehensively evaluated the achievements of the researchers in Khyber Pakhtunkhwa
Keywords: Researchers; Khyber Pakhtunkhwa; Poetry; Prose; Linguistics; Ghalibiyat; Iqbaliyat; Literature; Region; Quantity; Quality; Pashtun